Formação do professor para o uso de tecnologia assistiva - Manzini, Eduardo José [UNESP] (My University, 2013)
The specialized teachers' training to work in multifunctional resource classrooms still has to reach a satisfactory level. These teachers are expected to keep a set of resources and devices used to teach a wide range of students with different disabilities. That fact leads to reflection by the academic community. Thus what specific content should such training address? This paper aims to analyze the set of resources and equipment in a classroom and infer the teaching knowledge underlying their use. The analysis was conducted by classifying 63 resources and equipment items, which led to three categories: 1) set of materials that do not require academic knowledge; 2) set of materials that require academic knowledge related to any training course for teachers; 3) set of materials that require specific academic knowledge on working with students with disabilities. It concluded that around 36% of the resources do not require academic knowledge to be used; 35% of these resources and equipment require some academic knowledge to be properly handled, and around 29% of these resources and equipment require specific academic knowledge of their content. For instance, a specific training of those resources is necessary for acting with students with severe communication disorders, multiple disabilities and visual impairment or deafness.

A formação do professor especialista que atua em sala de recursos multifuncionais ainda não atingiu um nível desejado. Esse professor tem sob a sua guarda um kit de recursos e equipamentos para atender a uma ampla gama de alunos com diferentes deficiências, fato que é motivo de questionamento pela comunidade acadêmica. Assim, é possível perguntar: quais conteúdos específicos essa formação deveria abordar? O presente texto tem como objetivo analisar o kit dessa sala e inferir os saberes docentes subjacentes ao uso desses recursos e equipamentos. A análise, realizada a partir de uma classificação de 63 recursos e dos equipamentos,indicou três categorias: 1) materiais do kit que não demandam saber acadêmico; 2) materiais do kit que demandam saber acadêmico inerente a qualquer curso de formação de professores; 3) materiais do kit que demandam saber acadêmico específico para atendimento a alunos com deficiência. Conclui-se que por volta de 36% dos recursos não demandam saber acadêmico para serem utilizados; 35% desses recursos e equipamentos demandam saber acadêmico para o manuseio adequada; e por volta de 29% desses recursos e equipamentos demandam saber acadêmico específico desses conteúdos, ou seja, carecem de uma formação específica para atuação com alunos com severos distúrbios da comunicação, múltipla deficiência, deficiência visual e ou surdez.
Keywords: Educacao Especial; tecnologia assistiva; Formação de Professores